1993
DOI: 10.1002/hep.1840170513
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities in proximal small bowel motility in patients with cirrhosis

Abstract: Because altered intestinal motility could be involved in the pathogenesis of small intestine bacterial overgrowth observed in some patients with cirrhosis, we investigated fasting proximal small bowel motility in 16 cirrhotic patients and 8 healthy controls. In addition, the effects of oral tetracycline administration on duodenal motility were investigated in seven cirrhotic patients with evidence of bacterial overgrowth. The mean duration and characteristics of the migrating motor complex were analyzed. Cycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 20 publications
3
73
0
Order By: Relevance
“…34 Altered small intestinal motility was described in patients with cirrhosis. 18,35,36 Chang et al 25 have recently found that the frequency of motor migrating complex activity fronts and the motor migrating complex velocity were significantly higher in cirrhotic patients without SBP than in those with SBP. All these alterations in small intestinal motility could result, as we have found in the present study, in a prolonged intestinal transit time in cirrhotic patients when compared to normal controls, which in turn might facilitate the appearance of IBO.…”
Section: Discussionmentioning
confidence: 99%
“…34 Altered small intestinal motility was described in patients with cirrhosis. 18,35,36 Chang et al 25 have recently found that the frequency of motor migrating complex activity fronts and the motor migrating complex velocity were significantly higher in cirrhotic patients without SBP than in those with SBP. All these alterations in small intestinal motility could result, as we have found in the present study, in a prolonged intestinal transit time in cirrhotic patients when compared to normal controls, which in turn might facilitate the appearance of IBO.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from various studies has shown that altered intestinal motility may be involved in the pathogenesis of IBO in patients with liver disease (23,51), and could be associated with a higher incidence of SBP (24). A number of studies where the administration of prokinetic drugs caused a decrease in both IBO and BT point at the contribution of altered intestinal motility to these phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, selective intestinal decontamination with suppression of aerobic intestinal bacteria prevents BT in cirrhotic rats, and is the current prophylaxis for SBP in humans (17)(18)(19)(20). On the other hand, several studies have shown that impaired intestinal motility is one of the fac-tors contributing to enteric bacterial overgrowth, and also that intestinal transit is delayed in the setting of cirrhosis mainly related to the severity of disease (21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Manometry studies have described altered gut motility [88,193] in cirrhotics, whereas gastric emptying has been found to be delayed [74][75][76][77], normal [78][79][80] or accelerated [81]. Gastric accommodation has been reported to be impaired in patients with alcoholic cirrhosis [61] and cirrhotics with ascites [62] compared to healthy controls.…”
Section: Pathophysiology Of Gi Symptoms In Cirrhosis (Ii Iii)mentioning
confidence: 99%